2016
DOI: 10.1007/s00262-016-1801-1
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned from cancer vaccine trials and target antigen choice

Abstract: A wide variety of tumor antigens have been targeted in cancer immunotherapy studies. Traditionally, the focus has been on commonly over-expressed antigens shared across many patients and/or tumor types. As the field has progressed, the identity of human tumor rejection antigens has broadened. Immunologic monitoring of clinical trials has slowly elucidated candidate biomarkers of immune response and clinical response, and conversely, of immune dysfunction and suppression. We have utilized MART-1/Melan-A in our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 44 publications
0
17
0
1
Order By: Relevance
“…Thus, all these previous experiences with DC trials (and its failures) has led to the proposal that in order to realize the potential of DCs, it is important that multicenter phase II/III trials should be performed after standardizing the production of DC vaccines between centers [68]. The ability of DC vaccination to induce diverse neo-antigen specific T cell receptor (TCR) repertoire in terms of both TCR-β usage and clonal composition has also been implicated as one of the mechanism responsible for better tumor control [69], and needs to be considered for future immunomonitoring with the DC vaccine trials to establish its advantage over other immunotherapy regimens [70]. In addition, it has been suggested that strategy to incorporate DC-targeting via nanoparticles and combinatorial targeting of multiple human DC subsets may further improve the efficacy of DC vaccination [71].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, all these previous experiences with DC trials (and its failures) has led to the proposal that in order to realize the potential of DCs, it is important that multicenter phase II/III trials should be performed after standardizing the production of DC vaccines between centers [68]. The ability of DC vaccination to induce diverse neo-antigen specific T cell receptor (TCR) repertoire in terms of both TCR-β usage and clonal composition has also been implicated as one of the mechanism responsible for better tumor control [69], and needs to be considered for future immunomonitoring with the DC vaccine trials to establish its advantage over other immunotherapy regimens [70]. In addition, it has been suggested that strategy to incorporate DC-targeting via nanoparticles and combinatorial targeting of multiple human DC subsets may further improve the efficacy of DC vaccination [71].…”
Section: Discussionmentioning
confidence: 99%
“…Most antigens identified earlier as cancer-specific have been derived from self proteins. Investigated in hundreds of therapeutic clinical trials, these have been mostly clinically disappointing, partially due to central tolerance mechanisms and the elimination of high-avidity T-cells recognizing such normal proteins ( 3 6 ). In recent years, the remarkable clinical efficacy of the immune checkpoint blocking therapies has again motivated researchers to discover the immunogenic T-cell epitopes that mediate disease control or long-term cure ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…These include antigens such as Her2/Neu [70], mesothelin [71], lineage and tissue restricted differentiation antigens such as melanoma differentiation antigens (Tyrosinase Related Protein-2 and Melan-A (MART-1)) and Oncofetal antigens (Carcinoembryonic antigen) [72]. …”
Section: Figmentioning
confidence: 99%